Proposing a Model for Enhancing Financial and Operational Performance in Supply Chains - Naderian, Negar; Keramati, Mohamadali; Amin Mousavi , Seyed Abdollah (Management Strategies and Engineering Sciences, 2024)
This study aims to propose a model for improving the financial and operational performance of supply chains. The participants in this study were supply chain managers with a teaching experience of at least 15 years and holding a master's degree or higher. The selection of individuals was conducted using purposive sampling based on the criterion of teaching experience at the primary educational level. A total of 22 experts and specialists participated in the sampling process. Data were collected through semi-structured interviews, which continued until theoretical saturation was reached. Thematic analysis based on the Aterid-Sterling framework was used to analyze the qualitative data. To ensure validity, several criteria were employed, including Holsti's coefficient, Cohen's kappa index, Pi-Scott coefficient, and Krippendorff’s alpha, all of which were confirmed. Thematic analysis was performed using ATLAS.ti software. The results of the thematic analysis indicate that, from the 54 indicators (themes) identified, 13 primary themes were recognized, and two major themes were derived. The identified model included two primary themes: financial performance and operational performance within the supply chain. The 13 primary themes are: inventory management, financial reporting, financial actions at the operational level, coordination, risk management, sourcing strategy, demand planning, technology management, logistics strategy, customer interaction, flexibility, supplier communication management, and world-class quality. Given the critical importance of the supply chain in organizational success, enhancing its financial and operational performance is essential and fundamental. These improvements will lead to optimizing coordination among internal and external members, efficient logistics management, and sharing financial information, ultimately resulting in increased productivity, cost reduction, and enhanced competitiveness. Moreover, identifying and managing various risks, such as price risk, supplier risk, and market risk, are key actions that help effectively address environmental challenges and opportunities.